UPAYA MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM (IPA) TENTANG MAKHLUK HIDUP PADA PESERTA DIDIK KELAS III SDN 1 PADAAN MELALUI METODE MIND MAPPING - Supriono, Supriono (Universitas Negeri Semarang, 2016)
The problem of this research are learning centered on text book as the learning source, classical learning with speech method and learning without the relevant media, such as animal and plant posters. This research is Class Action Research (CAR) with 25 students as the research subject. The actions of the first cycle are presentation and discussion of the group task in a series. The actions of the second cycle are presentation and discussion of the group task in continuous. The results of this research are 1) the application of mind mapping method in Science learning is approaching group learning and carrying out the group task, 2) the group tasks are different pictures which fulfill with linked information, 3) the application of mind mapping method is followed with presentation and discussion, 4) the group task functions are as the relevant media and as a briefly, densely and clarity script, 5) the application of mind mapping method in Science learning is increasing the result study.